Evaluation Of Emergency Neonatal Obstetric Services (PONED) On The Degree Of Mother's Health In The Work Area Of The State Dolok Public Health Center, Silou District, Kahean, Simalungun Regency, In 2023 - Kristin Natalia Pasaribu; Novita Br Ginting Munthe (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Background: Mortality rates over time can describe the state and development of public health. Maternal Mortality Rate is one of the important indicators in determining the public health. Improving the health status of mothers and children (KIA) is still one of the main priorities in health development in Indonesia, due to the still high Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia.Objectives: to evaluate Basic Emergency Obstetric Neonatal Services (PONED) on Maternal Health Levels in the working area of ??the Dolok State Health Center, Silou Kahean District, Simalungun Regency in 2023.Research method: qualitative method with a qualitative descriptive approach that does not provide treatment to research subjects with the aim of obtaining a detailed picture of the subjects and using an in-depth interview method with informants that begins with observation and is accompanied by documentation to obtain research data.Results: The informant said that the supporting health equipment for PONED was available but not yet complete, while the equipment at the Dolok Public Health Center was mostly available and there were several equipment that did not function properly. The availability of human resources and facilities was good, but it required more attention for virgins in terms of function.Conclusion: The number of those who understand PONED at the Dolok Public Health Center is still lacking, the facilities and infrastructure at the PONED health center are quite adequate, and the implementation of obstetric and neonatal emergencies, PONED health workers are not on duty for 24 hours. Training and efforts to fulfill the needs of medical devices await realization.